A Translation Shift Analysis Of Verbs And Verb PhrasesIn The Book By Andrea Hirata "Edensor" - Permatasari, Fitria Intan; , Dr. Dwi Haryanti, M.Hum; , Mauly Halwat Hikmat, Ph. D (2014)
The purposes of this research are to classify the translation shifts of verbs and verb phrases in The book by Andrea Hirata "Edensor" and to explain the equivalence of verbs and verb phrases in The book by Andrea Hirata "Edensor". The type of this research is descriptive qualitative. The data of this research are sentences contain the verbs and verb phrases found in The Book by Andrea Hirata "Edensor". The researcher uses documentation to collect the data. The researcher also uses comparative method to analyze the data of the research. The result of this researchshows that there are 200 data that found by researcher. First, the data of translation of verb, there are 21 data or 10,5%; 3 data or 1,5% verb is translated into noun, 17 data or 8,5% verb is not translated, 1 datum or 0,5% verb is translated into noun phrase. Second, the data of translation of verb phrase, there are 179 data or 89,5%; 168 data or 84% verb is translated into verb phrase, 11 data or 5,5% verb phrase is translated into verb. Third, the researcher finds 197 data or 98,5% showing equivalence of translation and 3 data or 1,5% showing non-equivalence of translation.